Использование представителей семейства Apiaceae Lindl в качестве фиторемидиантов в условиях Приморского края (Дальневосточный федеральный округ) - Belousova N. M., Berseneva S. A., Iatsenko M. S. (Relevant lines of scientific research: theory and practice, 2016)
Possibilities of use typical for flora of Primorsky Krai the adventivnykh and native species of plants of family of the lands, umbrella for recultivation polluted by pollyutant of an anthropogenous origin are analysed.
Keywords: поллютанты; pollyutant; биоремедиация; bioremediation; фиторемедиация; фитоэкстракция; fitoremediation; phytoextraction; umbrella; семейство зонтичные